HUBUNGAN KEPEMIMPINAN KEPALA SEKOLAH DAN BUDAYA SEKOLAH DENGAN KINERJA GURU SD NEGERI DI KOTA LUBUKLINGGAU - Ria Putri Santri (UNIVERSITAS BENGKULU, 2016)
The objective of the research is to describe relationship between principal leadership and school culture with teacher performance at Elementary School. The subject is principals and teachers of The State of Elementary School in Lubuklinggau. The result obtained in this research were: (1) there was positive and significant relationship between principal leadership with teacherperformance with correlation coefficient was 0.801; (2) there was positive and significant relationship between school culture with teacher performance with correlation coefficient was 0.685; and (3) there was positive and significant relationship between the principal leadership and school culture with teacher performance with r square was 0.654. This means that the principal leadership and school culture has an influence on teacher performance of The State Elementary School in Lubuklinggau.Keywords: principal, leadership, school culture, and teacher performance